Effect of imidazole concentration and type of metal ion on the purification of recombinant green fluorescent protein using an affinity chromatography - Insyirah, Samsuddin (2014)
The purification of protein using IMAC can be influenced by imidazole concentration and type of metal ion. Different type of metal ion and different imidazole concentration will give different result of purity and yield for target protein. The strength of binding between histidine- tagged protein and metal ion is varies depending on the type of protein as well as the ion used. Imidazole is one of the competitive agents that are effective at displacing protein. Because of this, imidazole is one of the best agent to be used an eluent. Imidazole at low concentration is commonly use to minimise binding of host cell protein and at somewhat higher concentration, imidazole may also decrease the binding of histidine tagged- protein. This paper presents the effect of imidazole concentration and type of metal ion studies on the purification of recombinant green fluorescent protein (GFP) using an affinity chromatography. Escherichia coli (E.coli) BL21 (DE3) strain carrying the pRSETGFP plasmid encoding the GFP was grown in Luria-Bertani (LB) broth at 300C and 200 rpm for 16 hours. An induction of protein expression, Isopropyl β-ᴅ-1- thiogalactopyranoside when the cell density (OD600) reaches 0.6-0.8 enhanced the yield of functional GFP production. After harvesting, the cell suspension was disrupted using freeze and thaw method. Clarified GFP was then filter using nylon filter before being purified using a HisTrapTM FF 1 ml column (GE healthcare). The column was charged with different metal ion (0.1 M NiSO4 or CuSO4) and the concentration of imidazole at elution buffer was varied (100, 200, 300, 400, 500, 600 mM). For protein analysis, the sample was analysed using Lowry method for total protein determination, while amount of GFP was quantified using gel-based imaging method. This method has resulted in 95% purity at 500 mM imidazole concentration and 93% recovery of GFP at 300 mM imidazole concentration when the column was charged with Ni(II) ion while 89% purity at 500 mM imidazole concentration and 95 % recovery at 400 mM at imidazole concentration of GFP when the column was charged with Cu(II) ion